A Qualitative Systematic Review of Effects of Provider Characteristics and Nonverbal Behavior on Pain, and Placebo and Nocebo Effects - Daniali, Hojjat; Flaten, Magne Arve (Frontiers in Psychiatry, 2019)
Background Previous research has indicated that the sex, status, and non-verbal behaviors of experimenters or clinicians can contribute to reported pain, and placebo and nocebo effects in patients or research participants. However, no systematic review has been published. Objective: To investigate the effects of experimenter/clinician characteristics and non-verbal behavior on pain, placebo, and nocebo effects. Methods: Using EmBase, Web of Knowledge, and PubMed databases, several literature searches were conducted to find studies that investigated the effects of the experimenter’s/clinician’s sex, status and non-verbal behaviors on pain, placebo, and nocebo effects. Results: Thirty-four studies were included, twenty on the effects of characteristics of the experimenter/clinician, eleven on the role of non-verbal behaviors, and three on the effects of both non-verbal behaviors and characteristics of experimenters/clinicians on pain and placebo/nocebo effects. Experimenters/clinicians induced lower pain report in participants of the opposite sex. Furthermore, higher confidence, competence, and professionalism of experimenters/clinicians resulted in lower pain report and higher placebo effects, whereas lower status of experimenters/clinicians such as lower confidence, competence, and professionalism generated higher reported pain and lower placebo effects. Positive non-verbal behaviors (e.g. smiling, strong tone of voice, more eye contact, more leaning toward the patient/participant, and more body gestures) contributed to lower reported pain and higher placebo effects, whereas negative non-verbal behaviors (i.e. no smile, monotonous tone of voice, no eye contact, leaning backward from the participant/patient, and no body gestures) contributed to higher reported pain and nocebo effects. Conclusion: Characteristics and non-verbal behaviors of experimenters/clinicians contribute to the elicitation and modulation of pain, placebo and nocebo effects.